An Age of Contradiction, or Who Killed Colonel Protheroe?. (September 2021) - Rolls, Alistair
Abstract : Crime Fiction studies have entered something of a new age. It is no longer necessary to begin an article with defensive remarks about sales numbers or the literary qualities of detective novels; indeed, this may be the start of a new Golden Age. In this article, I shall review two phenomena that may be considered instrumental in this critical turn: adaptations for the screen and Pierre Bayard's self-styled critique policière, or 'detective criticism'. Screen adaptations of Agatha Christie's works have, by turns, enthralled and dismayed viewers. In removing their cosy edges and transforming Christie's novels into films fit for contemporary audiences, they have gone as far, in some cases, as to change the sacrosanct ending. Here, I shall discuss the ways in which Charlie Palmer's 2004 adaptation of The Murder at the Vicarage points to a potential rereading of the novel. I shall then deploy Bayardian detective criticism not only to demonstrate the implausibility of Miss Marple's final solution to The Murder at the Vicarage, but also to suggest that Christie's greatest skill lies perhaps in saving her greatest red herring until last.